Interconnected TiO2 Nanowire Networks for PbS Quantum Dot Solar Cell Applications - Fan Xu; Jaime Benavides; Xin Ma; Sylvain G. Cloutier (Journal of Nanotechnology)
We present a simple method for the fabrication of an interconnected porous TiO2 nanostructured film via dip coating in a colloidal suspension of ultrathin TiO2 nanowires followed by high-temperature annealing. The spheroidization of the nanowires and the fusing of the loosely packed nanowire films at the contact points lead to the formation of nanopores. Using this interconnected TiO2 nanowire network for electron transport, a PbS/TiO2 heterojunction solar cell with a large short-circuit current of 2.5 mA/cm2, a Voc of 0.6 V, and a power conversion efficiency of 5.4% is achieved under 8.5 mW/cm2 white light illumination. Compared to conventional planar TiO2 film structures, these results suggest superior electron transport properties while still providing the large interfacial area between PbS quantum dots and TiO2 required for efficient exciton dissociation.